ANALISIS POLA KEMITRAAN USAHATANI UBI KAYU DI DESA PUDING BESAR KECAMATAN PUDING BESAR KABUPATEN BANGKA - Yansah, Yansah; Setiawan, Iwan; Pranoto, Yudi Sapta (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2020)
This study aims to describe the implementation of the partnership farming Cassava Village Pudding Besar District of pudding Big Bangka, analyze the differences in average income that is obtained by farmers from various partnership schemes cassava in the village Pudding Besar District of pudding Big Bangka, analyzed the factors - factors that influence farmers' decision in choosing partners and not partner with partnership cassava farm in the village of Great pudding pudding Large District of Bangka. This study was conducted in January 2019 until January 2020 in the village of Great Pudding Pudding Large District of Bangka. The method used is survey method. Penrikan method used example is a method of quota sampling with a sample of two groups of 40 people and the partnering farmers do not partner 40 people. Methods of data analysis using descriptive qualitative, quantitative analsisis (independent sample t-test, binary logistic regression). The results showed the implementation of partnership farming patterns occurring in the village of Great Pudding is a partnership with the name intiplasma KSR Program (Cassava People's Gardens). There is a real difference but not significant, the average income of Rp 32,384,718 partner farmers, while the non- partner farmers Rp 36,751,056 with the difference in the average income of farmers partner and non- partner Rp 4,366,388 per year. Factors that significantly affect farmers' decisions in partnering and partnering as age and availability of capital.